Pharmacokinetics and Bioequivalence of Two Formulations of Azithromycin Tablets: A Randomized, Single-Dose, Three-Period, Crossover Study in Healthy Chinese Volunteers Under Fasting and Fed Conditions - Yingrong Chen; Libing Ye; Jue Mei; Mengli Tian; Min Xu; Qiuyue Jin; Xiang Yu; Shuixin Yang; Jie Wang (Adis, Springer Healthcare, 2024)
Abstract Background and Objective Azithromycin is the first azalide antibiotic that is related to the macrolide family of antibiotics. Bioequivalence studies in China are initiated by the National Medical Products Administration (NMPA), which supports a generic consistency evaluation program for ensuring that generic products manufactured in China meet the required standards and provide equivalent therapeutic effects to their reference products. This study aimed to assess the bioequivalence of two azithromycin tablets under both fasting and fed conditions in healthy Chinese volunteers. Methods This was a single-center, open-label, single-dose, randomized, three-way crossover trial with two independent groups (fasting group and fed group). A total of 72 healthy Chinese subjects (36 subjects in the fasting state and 36 subjects in the fed state) were enrolled and randomized to treatment. Blood samples were collected from 0 to 120 h after a single oral dose of a 250-mg generic azithromycin tablet (test, T) or branded azithromycin tablet (reference, R). The plasma concentrations of azithromycin were determined by high-performance liquid chromatography-tandem mass spectrometry (HPLC‒MS/MS). A non-compartmental analysis method was used to estimate the pharmacokinetic parameters. Adverse events were documented. Results In a fasting state, the bioequivalence of maximum plasma concentration (C max) was evaluated using the reference-scaled average bioequivalence (RSABE) approach (within-subject standard deviation, S WR > 0.294), and the bioequivalence of area under the concentration-time curve from time 0 to the time of the last measurable plasma concentration (AUC0-t ) and area under the concentration-time curve from time 0 extrapolated to infinity (AUC0-∞ ) were evaluated by the average bioequivalence (ABE) method (S WR <  0.294). The geometric mean ratio (GMR) of T/R for C max was 106.49%, while the 95% upper confidence bound was <  0. The GMRs of AUC0-t and AUC0-∞ were 103.34% and 101.28%, and the 90% confidence intervals (CIs) of the test/reference were 95.90-111.35%/94.85-108.15%, respectively. In the fed state, the RSABE approach was applied to estimate the bioequivalence of C max (S WR >0.294), and the ABE approach was applied to estimate the bioequivalence of AUC0-t and AUC0-∞ (SWR <  0.294). The GMR for C max was 99.80%, while the 95% upper confidence bound value was <  0. The GMRs of AUC0-t and AUC0-∞ were 97.07% and 98.15%, and the 90% CIs of the T/R were 90.02-104.68% and 90.66-106.25%, respectively. All adverse events were mild and transient. Conclusions The trial indicated that the test and the reference azithromycin tablets were bioequivalent and well tolerated in healthy Chinese volunteers under both fasting and fed conditions. Trial Registration Clinicaltrials, ChiCTR2300071630 (retrospectively registered in 19/05/2023).